The introduction of elephant into medium-sized conservation areas - Anderson, Jeremy (Pachyderm, 1993)
The reintroduction of elephants should only be considered if one of the objectives of the reserve is to re-establish the wildlife community, and the species formerly occurred in the vicinity. Secondary factors include the ecological role played by elephants, and the value of this species to visitors. The experiences of the large scale reintroductions in Pilanesberg National Park and the Hluhluwe/Umfolozi Complex are described, inclusive of the problems encountered and likely to arise in a project of this nature.